Impact of Digital Marketing Tools in Customer Purchase Decision towards Shopping Goods in Dhaka City - Kamal, Abu Hena Md. Mustafa; Hossain, Md. Ujjal; Maruf, Saleh Mohammed (International Journal of Business, Management and Economics, 2025)
This paper is used to discover the digital marketing tool which affect Consumer buying behavior towards shopping goods. This survey is a part of discovering the factors that affect consumer mind. Firstly a model is created for doing the study properly and then data are analyzed using Likert Scale (5 point rating scale).Secondly Frequency distribution and the percentage have been shown to analyze demographic state of the respondents. Thirdly to measure to get some extra information and getting clear idea about data descriptive statistic such as mean and standard deviation has been used. Finally multiple regression analysis is used to know which factor has significant impact on consumer purchasing behavior. SPSS 20.0 has been used to analyze all the data. The findings of the study shows that, people buy products through digital marketing tools if the website is trusted and user friendly. Besides most of the people are aware of digital marketing tools